2015
DOI: 10.1083/jcb.201407130
|View full text |Cite
|
Sign up to set email alerts
|

TAGLN2 regulates T cell activation by stabilizing the actin cytoskeleton at the immunological synapse

Abstract: TAGLN2 stabilizes cortical F-actin and thereby maintains F-actin contents at the immunological synapse, which allows T cell activation following T cell receptor stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(121 citation statements)
references
References 42 publications
4
116
1
Order By: Relevance
“…17 In the present study, we also found that TAGLN2 was physically associated with LFA-1 through its CH domain, regardless of stimulation (Figure 1(d,e)), and corresponded to the activation of Rap1 (Figure 1(f)), which functions as a key regulator of LFA-1-dependent adhesion and migration of T cells. 1820 These results suggested that TAGLN2, in addition to its biochemical characteristics enabling it to control actin dynamics, acted as a cytosolic factor to modulate ‘inside-out’ signaling of the integrin LFA-1.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…17 In the present study, we also found that TAGLN2 was physically associated with LFA-1 through its CH domain, regardless of stimulation (Figure 1(d,e)), and corresponded to the activation of Rap1 (Figure 1(f)), which functions as a key regulator of LFA-1-dependent adhesion and migration of T cells. 1820 These results suggested that TAGLN2, in addition to its biochemical characteristics enabling it to control actin dynamics, acted as a cytosolic factor to modulate ‘inside-out’ signaling of the integrin LFA-1.…”
Section: Resultssupporting
confidence: 75%
“…16 Among three TAGLN superfamily members, we recently reported that TAGLN2 is predominantly expressed in T cells and stabilizes cortical F-actin to maintain the IS. 17 We also found that TAGLN2 overexpression caused LFA-1 activation after TCR stimulation. 17 In the present study, we found that TAGLN2 physically associated with LFA-1 via its calponin homology (CH) domain and enhanced the activity of Rap1, a small GTPase that has been shown to regulate LFA-1 affinity and clustering.…”
Section: Introductionmentioning
confidence: 51%
See 3 more Smart Citations